Influencia de las tecnologías de información y comunicación (TIC) en el aprendizaje colaborativo de los jóvenes de 9º y 10º de la Unidad Educativa 23 de Junio del cantón Baba Provincia Los Ríos - Bravo Sellan, Rody Lenin (2019)
The present research work analyzes the appropriate use of information and communication technologies in the educational field, because it is a tool that allows the teacher to develop skills, and knowledge that help them to develop in the social field and in Your daily live. Because the correct use of the technological tools, the teacher who is in charge of the learning of the students has a great part of responsibility, must be able to master and put into practice everything learned to improve the collaborative learning of the youth of the unit . The outcome of this research determined that (ICTs) are an indispensable tool for the learning process, both for students and teachers of this educational institution. Therefore, it leads us to the result of the implementation of a guide of Information Technology and Communication to strengthen the collaborative learning of young people